2005
DOI: 10.1007/s10658-004-2877-6
|View full text |Cite
|
Sign up to set email alerts
|

Genotype � environment interactions in symptom development and yield of cassava genotypes with artificial and natural cassava bacterial blight infections

Abstract: Thirty-seven cassava genotypes from Benin, including advanced breeding lines, were tested for their reaction to bacterial blight in the forest-savanna transition, wet savanna and dry savanna zones of Benin. Sixteen genotypes were repeated in 12 environments. In year 1998, genotypes RB92164, RB92022, TMS30572, BEN86004, RB92033 and Dangbo2, and in year 2000, genotypes RB92202, RB92151, RB92132 and TMS30572 were resistant in one ecozone. Among the more resistant genotypes, CAP94030, BEN86040, RB89509, RB92132 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
1
26
0
1
Order By: Relevance
“…For wax analysis The fourth leaf from the top was collected from randomly selected 11 months-old cassava plants of genotypes BEN86052 and TMS30572, and of genotypes RB92132, CAP92034, CAP94030, RB92004 and BEN86040 (moderately) resistant to cassava bacterial blight (Zinsou et al, 2005), with five leaves per genotype and three replicates.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…For wax analysis The fourth leaf from the top was collected from randomly selected 11 months-old cassava plants of genotypes BEN86052 and TMS30572, and of genotypes RB92132, CAP92034, CAP94030, RB92004 and BEN86040 (moderately) resistant to cassava bacterial blight (Zinsou et al, 2005), with five leaves per genotype and three replicates.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In previous studies (Zinsou et al, 2005), these genotypes were evaluated for numbers of leaves with spots or blight, dropped/wilted leaves and stems with dieback symptoms at a monthly interval with a gap over the dry season. The severity index in days over 12 months was calculated according to the following formula:…”
Section: Symptom Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the results reveal the narrow basis for resistance to bacterial blight in local improved cassava varieties from Benin. Considering disease reaction and root yield across environments, only genotype TMS30572 was consistently moderately resistant to resistant and high-yielding in different environments [88]. Thus, genotype TMS30572 can be recommended to farmers.…”
Section: Cultural Measuresmentioning
confidence: 99%
“…Our results in Benin showed that differences in environmental conditions may have an influence on wax quantities and thereby, contribute to the high genotype x environment interactions in cassava [88]. Stomatal anatomy was reported to confer resistance to some varieties against certain of their bacterial pathogens [92].…”
Section: Resistance Mechanismsmentioning
confidence: 99%